Commuting, children and the gender wage gap - Malte Borghorst; Ismir Mulalic; Jos van Ommeren (Tinbergen Institute, 2021)
It has been documented that the gender pay gap strongly increases after the birth of the first child. We focus on Denmark and show that gender differences regarding commuting play an important role in explaining this. We offer 3 pieces of evidence. First, the gender pay and commuting gaps come into existence at the same moment: when the first child is born. Second, wage compensation for commuting is lower for women after the birth compared to men: about 3 − 4 percentage points of the overall gender pay gap is due to gender differences related to compensation for commuting when having children. Third, women who get a child are much more likely to leave their job when they have a long commute, which is not true for men. Using information on job moving through the lens of a dynamic search model, these results imply that the marginal cost of commuting increases substantially for women with a child. For female workers with a child, a one standard deviation increase in commuting distance induces costs equivalent to about 10% of their wage, whereas for all other workers these costs are equivalent to only 3-4% of their wages.
Keywords: J31; R41; J61; R23; 330; commuting; wages; gender wage gap